2017
DOI: 10.1002/ejic.201700192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi‐Carborane Substitution on the Photophysical and Electron‐Accepting Properties of o‐Carboranylbenzene Compounds

Abstract: Multiple o‐carborane substituted compounds, mono‐, 1,3‐bis‐, and 1,3,5‐tris[2‐(4‐butylphenyl)‐o‐carboran‐1‐yl]benzene (1–3), were prepared and characterized by multinuclear NMR spectroscopy and elemental analysis. The solid‐state structures of 2 and 3 were also confirmed by single‐crystal X‐ray diffraction. While the mono‐carborane compound 1 was nonemissive in the solution state at 298 K, the photoluminescence (PL) spectra of 2 and 3 exhibited weak‐to‐moderate emission (λem = 352 nm for 2 and 363 nm for 3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…We note that B3LYP has been widely preferred for the excited-state investigation of o -CB– Ant as well as other carborane–fluorophore systems. 24 , 28 33 , 40 , 42 , 47 , 68 70 In general, this functional shows good agreement for the absorption and emission energies of these systems. However, one should also note that it can sometimes be problematic for pure CT states as it is shown to underestimate the excited-state energies for such transitions.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…We note that B3LYP has been widely preferred for the excited-state investigation of o -CB– Ant as well as other carborane–fluorophore systems. 24 , 28 33 , 40 , 42 , 47 , 68 70 In general, this functional shows good agreement for the absorption and emission energies of these systems. However, one should also note that it can sometimes be problematic for pure CT states as it is shown to underestimate the excited-state energies for such transitions.…”
Section: Methodsmentioning
confidence: 72%
“…40 , 41 While the o -carborane–fluorophore adducts typically exhibit low photoluminescence quantum yields in varied solutions, a unique enhanced emission behavior can be observed in the solid-state (i.e., aggregation-induced emission). 33 , 38 , 42 44 This has been discussed in the previous literature that restricting the undesired vibrations of o -carborane’s “C–C” bond in the aggregate state leads to enhanced photoluminescence quantum yields. In addition, it has been shown that the enhancement in emission could also be achieved in the solution phase via structural modifications on o -carborane to limit o -carborane’s “C–C” bond elongation, which plays a critical role in emission quenching mechanisms.…”
Section: Introductionmentioning
confidence: 94%
“…o -Carborane (C 2 B 10 H 12 ), an icosahedral boron cluster, possesses unique electronic, steric, and chemical properties, including high hydrophobicity, high thermal and chemical stabilities, and strong electron-accepting characteristics. ,− Integration of carborane into aromatic polymeric backbones has been shown to drastically influence the emission properties of these systems. In many cases, changes in the emission properties arise due to the formation of an intramolecular charge-transfer (ICT) state between the aromatic moiety and the carborane molecule. , The ICT state is typically characterized by the appearance of an additional red-shifted emission band in the photoluminescence (PL) spectra that experiences solvatochromic behavior and/or aggregation-induced emission (AIE), AIE enhancement (AIEE), , , or crystallization-induced emission enhancement (CIEE). ,, The emission intensity of the ICT state can also be influenced by twisting between the plane of the aromatic excited state and the C1–C2 bond of the carborane molecule [twisting-induced charge transfer (TICT)]. , Furthermore, the ICT state is typically composed of charged species, making it polar in nature. ,, …”
Section: Introductionmentioning
confidence: 99%
“…51−53 In many cases, changes in the emission properties arise due to the formation of an intramolecular charge-transfer (ICT) state between the aromatic moiety and the carborane molecule. 2−5,31−33 The ICT state is typically characterized by the appearance of an additional red-shifted emission band in the photoluminescence (PL) spectra that experiences solvatochromic behavior and/or aggregationi n d u c e d e m i s s i o n ( A I E ) , A I E e n h a n c e m e n t (AIEE), [6][7][8][9][34][35][36]42 or crystallization-induced emission enhancement (CIEE). 10,27,30 The emission intensity of the ICT state can also be influenced by twisting between the plane of the aromatic excited state and the C1−C2 bond of the carborane molecule [twisting-induced charge transfer (TICT)].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent works, it was observed that the aryl-modified o -carboranes provided extremely intense luminescence with almost quantitative efficiencies, even in the solid state [ 27 , 28 , 29 ]. Moreover, it was shown that multi-carborane substitutions onto benzene induced AIE and solid-state luminescence [ 43 ]. On the basis of these results, we presumed that the introduction of multiple o -carborane units into the strong electron-donating unit might be effective for realizing intense AIE.…”
Section: Introductionmentioning
confidence: 99%